Commonwealth Caribbean Family Law husband, Wife and Cohabitant: Book Review - Ilma, Cholifatul; Triana, Yunika (Journal of Islamic Studies and Education, 2024)
"Commonwealth Caribbean Family Law: Husband, Wife, and Cohabitant" by Karen Nunez-Tesheira, published by Routledge in 2016, is part of the Commonwealth Caribbean Law Series. This comprehensive book delves into the intricate legal landscape surrounding family relationships in the Commonwealth Caribbean region. With a focus on the rights, obligations, and protections of husbands, wives, and cohabitants, Nunez-Tesheira likely explores various aspects of family law, including marriage, divorce, property rights, child custody, and maintenance. The book structured to provide a thorough examination of relevant statutes, case law, and legal principles, offering insights into the complexities of familial dynamics within the Caribbean context. Through meticulous analysis and scholarly research, Nunez-Tesheira's work likely serves as a valuable resource for legal practitioners, scholars, and students seeking to understand the legal framework governing family relationships in the Commonwealth Caribbean.